Design and implementation of an affordable, public sector electronic medical record in rural Nepal. Issue 2 (1st April 2017) - Raut, Anant; Gauchan, Bikash; Yarbrough, Chase; Schwarz, Dan; Citrin, David; Singh, Vivek; Verma, Varun; Hawley, Jessica; Bangura, Alex Harsha; Shrestha, Biplav; Schwarz, Ryan; Adhikari, Mukesh; et al.
Abstract : Introduction: Globally, electronic medical records are central to the infrastructure of modern healthcare systems. Yet, the vast majority of electronic medical records have been designed for resource-rich environments and are not feasible in settings of poverty. Here, we describe the design and implementation of an electronic medical record at a public sector district hospital in rural Nepal and its subsequent expansion to an additional public sector facility. Development: The electronic medical record was designed to solve for the following elements of public sector healthcare delivery: 1) integration of the systems across inpatient, surgical, outpatient, emergency, laboratory, radiology and pharmacy sites of care; 2) effective data extraction for impact evaluation and government regulation; 3) optimization for longitudinal care provision and patient tracking and 4) effectiveness for quality improvement initiatives. Application: For these purposes, we adapted Bahmni, a product built with open-source components for patient tracking, clinical protocols, pharmacy, laboratory, imaging, financial management and supply logistics. In close partnership with government officials, we deployed the system in February of 2015, added on additional functionality and iteratively improved the system over the following year. This experience enabled us then to deploy the system at an additional district-level hospital in a different part of the country in under four weeks. We discuss the implementation challenges and the strategies we pursued to build an electronic medical record for the public sector in rural Nepal. Discussion: Over the course of 18 months, we were able to develop, deploy and iterate upon the electronic medical record, and then deploy the refined product at an additional facility within only four weeks. Our experience suggests the feasibility of an integrated electronic medical record for public sector care delivery even in settings of rural poverty.